1972
DOI: 10.3171/jns.1972.36.1.0001
|View full text |Cite
|
Sign up to set email alerts
|

Experience with brain abscesses

Abstract: Eighty-six patients with brain abscesses were seen at the University of Minnesota Hospitals from 1946-1965, and 46 died, a 53% mortality. Multiple and brain stem abscesses accounted for several fatalities, while delayed and missed diagnosis accounted for one third of the deaths. Evidence of infection was often minimal in patients with brain abscess. Lumbar puncture as a diagnostic tool was inaccurate and occasionally fatal. Brain scan, electroencephalography, and angiography were the best diagnostic tests. Dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
2

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(45 citation statements)
references
References 16 publications
1
41
1
2
Order By: Relevance
“…On the contrary, the 10% rate of our series should be compared to the 15% of Belter et al [1973] and to the 38% in the pediatric series of Carey et al [1972], One fact should be pointed out in the present study: the 17% rate of mental sequelae. However, all these low IQs were found in children with cyanotic heart disease.…”
Section: Discussioncontrasting
confidence: 68%
“…On the contrary, the 10% rate of our series should be compared to the 15% of Belter et al [1973] and to the 38% in the pediatric series of Carey et al [1972], One fact should be pointed out in the present study: the 17% rate of mental sequelae. However, all these low IQs were found in children with cyanotic heart disease.…”
Section: Discussioncontrasting
confidence: 68%
“…19 Moreover, many authors have reported that brain abscesses in children cause cognitive deficits. 14,15,19 These authors also document that a poorer prognosis in terms of normal intellectual development is expected in younger children…”
Section: Prognosismentioning
confidence: 88%
“…Carey et al 6 . reported impaired scholastic ability in 70% of children tested 6 years after surgery.…”
Section: Discussionmentioning
confidence: 99%